Implementation of Peer To Peer Supervision in Developing Competencies of Junior High School and Madrasah Tsanawiyah Teachers in Sekarbela District, Mataram - Supatah, Supatah; Fitriani, Moh. Iwan; Thohri, Muhammad (Jurnal Ilmiah Profesi Pendidikan, 2024)
This study aims to explore the implementation of peer-to-peer supervision in developing teacher competencies at SMPN 17 Mataram and MTSN 3 Mataram. This research method employs a qualitative approach with a case study design. Data collection techniques include observation, interviews, and documentation. Data were analyzed using thematic analysis. The results of the study indicate that peer-to-peer supervision is effective in developing various teacher competencies, such as collaboration, communication, pedagogical knowledge, and technology integration. The positive outcomes include improved teacher competencies, conducive learning environments, and increased teacher comfort in facing evaluations. However, challenges include the lack of objectivity in assessments, suboptimal follow-up after supervision, and absence of an official schedule, affecting effectiveness. The implications emphasize the importance of implementing peer-to-peer supervision to enhance the quality of education in secondary schools. Future research could focus on addressing challenges and further exploring the impact of peer-to-peer supervision.